Tackling the global education crisis: the UBS Optimus Foundation’s use of social finance (2019)
Around 264 million children and adolescents are not in school, and only one in 12 young people in low-income countries is on track to gain secondary level skills (UNESCO, 2017). Some progress in achieving gender equality has been made, but far more girls than boys still do not have access to an education (UNESCO, 2015). More alarmingly, estimates show that more than 617 million children and adolescents are not achieving minimum proficiency levels in reading and mathematics (UNESCO Institute of Statistics, 2017). Warning of a learning crisis in global education, the recent World Development Report noted: This learning crisis is a moral crisis. When delivered well, education cures a host of societal ills. For individuals, it promotes employment, earnings, health, and poverty reduction. For societies, it spurs innovation, strengthens institutions, and fosters social cohesion. But these benefits depend largely on learning. Schooling without learning is a wasted opportunity. More than that, it is a great injustice: the children whom society is failing most are the ones who most need a good education to succeed in life. (World Bank, 2018, p. 3)